Solve for y 8y+3=6y-3

Math
8y+3=6y-3
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 6y from both sides of the equation.
8y+3-6y=-3
Subtract 6y from 8y.
2y+3=-3
2y+3=-3
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
2y=-3-3
Subtract 3 from -3.
2y=-6
2y=-6
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2y=-6 by 2.
2y2=-62
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2y2=-62
Divide y by 1.
y=-62
y=-62
Divide -6 by 2.
y=-3
y=-3
Solve for y 8y+3=6y-3

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top